Health Conditions for Medical Assessment in Commercial Drivers - Mitprasit, Amporn; Soonthornvinit, Warisa; Kunawudhi, Garnchit (Journal of Preventive Medicine Association of Thailand, 2025)
This academic review article focuses on the importance of health conditions or medical requirements for public transport drivers as established by the Department of Disease Control through Memorandum of Agreement between the Ministry of Public Health and the Ministry of Transport in Thailand. The essential criteria comprise physical fitness such as vision, sensory impairments, and the management of chronic conditions such as hypertension and diabetes, as well as acute medical conditions that pose risks on the road, especially epilepsy, which can cause sudden unconsciousness, which is a significant cause of vehicle-related accidents. Additionally, the assessment includes mental health evaluation and the screening of alcohol and substance use. The authors have compiled assessment criteria from various countries to demonstrate different approaches to these requirements. These health considerations play a crucial role in preventing accidents and ensuring the safety of both public transport drivers and the public.